Synergistic efficacy and safety of PD-1/PD-L1 inhibitors combined with nab-paclitaxel and platinum chemotherapy in NSCLC: A systematic review and meta-analysis of randomized controlled trials - Shen, Yijing (Frontiers in Oncology, 2025)
BackgroundNon-small cell lung cancer (NSCLC), the leading cause of cancer mortality, often requires platinum-based chemotherapy. Nanoparticle albumin-bound paclitaxel (nab-paclitaxel) improves drug delivery, while PD-1/PD-L1 inhibitors enhance antitumor immunity. Preclinical studies suggest synergy, but clinical evidence for combining these agents remains limited.MethodsFollowing PRISMA guidelines, this meta-analysis pooled data from four randomized controlled trials (1998 patients). Databases (PubMed, Embase, Cochrane Central, web of science) were searched until January 2025. Trials comparing PD-1/PD-L1 inhibitors + nab-paclitaxel-platinum (experimental) versus chemotherapy alone (control) were included. Outcomes included including objective response rate (ORR), progression-free survival (PFS), overall survival (OS), pathologic complete response (pCR), major pathologic response (MPR), and grade ≥3 adverse events (AEs). Statistical analyses used fixed/random-effects models.ResultsThe combination therapy significantly improved ORR (OR = 1.81, 95% CI: 1.49–2.20, p < 0.001), PFS (HR = 0.65, 95% CI: 0.58–0.73), and OS (HR = 0.81, 95% CI: 0.72–0.91). In the resectable setting, neoadjuvant treatment resulted in higher pathologic complete response (pCR: 32.6% vs. 8.9%) and major pathologic response (MPR: 65.1% vs. 15.6%). Subgroup analyses showed enhanced benefit in PD-L1-high patients. The experimental group had increased risk of grade ≥3 thrombocytopenia (RR = 1.83) and immune-related adverse events (RR = 2.49).ConclusionPD-1/PD-L1 inhibitors combined with nab-paclitaxel-platinum enhance survival outcomes in NSCLC, particularly for PD-L1-high patients. Despite increased immune-related toxicity risks, this regimen represents a promising first-line option, warranting biomarker-driven selection and vigilant AE management. Future studies should address heterogeneity in platinum agents and optimize patient stratification.